2015
DOI: 10.3390/f6051721
|View full text |Cite
|
Sign up to set email alerts
|

A Benchmark of Lidar-Based Single Tree Detection Methods Using Heterogeneous Forest Data from the Alpine Space

Abstract: Abstract:In this study, eight airborne laser scanning (ALS)-based single tree detection methods are benchmarked and investigated. The methods were applied to a unique dataset originating from different regions of the Alpine Space covering different study areas, forest OPEN ACCESSForests 2015, 6 1722 types, and structures. This is the first benchmark ever performed for different forests within the Alps. The evaluation of the detection results was carried out in a reproducible way by automatically matching them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
215
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(228 citation statements)
references
References 31 publications
12
215
0
1
Order By: Relevance
“…Pelizzano consists of multi-storied mixed forest that has a large amount of trees with different height layers. In contrast, the best detection result occurred in a single-storied coniferous forest (Eysn et al 2015). Warner et al (1998) and Park et al (2014) also mentioned that various types of forest conditions could result in distinctly different results due to different crown morphology characteristics.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Pelizzano consists of multi-storied mixed forest that has a large amount of trees with different height layers. In contrast, the best detection result occurred in a single-storied coniferous forest (Eysn et al 2015). Warner et al (1998) and Park et al (2014) also mentioned that various types of forest conditions could result in distinctly different results due to different crown morphology characteristics.…”
Section: Introductionmentioning
confidence: 95%
“…Most recent studies on tree detection can be categorized to five main methods: local maxima (LM) filtering (Popescu et al 2002), region-growing , valley-following (Gougeon 1995), watershed segmentation (Kwak et al 2007), and the integrated methods relying on LM (Eysn et al 2015). LM filtering has been widely used to detect trees in remotely sensed images (Pouliot et al 2002;Park et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, algorithms for automatic identification of the individual trees (tree detection) have been continuously improving, using 2D or 3D segmentation of LiDAR data or a combination of LiDAR data and aerial or satellite imagery. Eysn et al (2015) found that forest structure has a significant influence on the tree identification results, with the highest matching rate (86% RMS) for single-layered coniferous and the lowest matching rate (47% RMS) for single-layered mixed forests. Various studies have demonstrated the utility of LiDAR technology for the estimation of height, stand basal area, total tree biomass or foliage biomass mainly in coniferous stands (Hall et al, 2005;Lefsky et al, 2005;García et al, 2010;Edson and Wing, 2011).…”
Section: Ground Reference Datamentioning
confidence: 99%